The tourist ecosystem through social networks - Barrientos Báez, Almudena; Bonales Daimiel, Gema; Caldevilla-Domínguez, David (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
The covid-19 pandemic generated serious economic repercussions in the tourism sector, for which it had to accentuate the use of social networks in its communication. The study focuses on the analysis of the three destinations selected as the safest to travel during the summer of 2020 according to the eleventh edition of the European Best Destinations competition (2020). Special emphasis has been placed on the idea of a "safe destination" and how tourists themselves -microinfluencers- have joined in making the messages viral through their comments, reactions and publications. The main conclusion obtained is that thanks to this visibility strategy, countries have contributed to creating the image of a safe ecosystem, achieving notoriety and strengthening the country-image, achieving an impact on a global level.